Structural and Electronic Properties of Polyoxovanadoborates Containing the [V 12 B 18 O 60 ] Core in Different Mixed Valence States - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Muñoz-Becerra, K; Muñoz-Becerra, K (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
This review summarizes all published data until April 2015 related to crystalline lattices formed by the [V 12 B 18 O 60 ] core, which generates polyanionic clusters with different degrees of protonation and mixed-valence ratios. The negative charge of this cluster is counterbalanced by different cations such as protonated amines, hydronium, and alkaline, and transition metal ions. The cluster is shown to form extended 1D, 2D, or 3D frameworks by forming covalent bonds or presenting hydrogen bond interactions with the present secondary cations. These cations have little influence on the solid state reflectance UV-visible spectra of the polyanionic cluster, but are shown to modify the FT-IR spectra and the magnetic behavior of the different reported species. ©. © 2015 by the authors.